Analysis Of The Traditional Lamang Broadcastang Cake In Sariak Alahan Tigo - Yunica, Febria; Faridah, Anni; Gusnita, Wiwik; Indrayeni, Wiwik (Universitas Negeri Padang, 2024)
This research is motivated by traditional cakes which are rarely found because most people tend to like ready-to-eat food. In the economic world, selling traditional cakes is less popular with the public, this has resulted in the lack of existence of traditional cakes. Like Lamang Siarang, it is rarely known by the wider community because this traditional cake itself is only made on certain occasions and the manufacturing process is complicated and takes quite a long time. The aim of this research is to describe the tools, materials, method of making, meaning and quality in making lamang broadcastang. The type of research used in this research is descriptive qualitative. Using observation, interview and documentation techniques. The instrument of this research is the researcher himself as a data collection tool. The number of informants taken was 15 informants. From older mothers, mothers who are experts in making lamang and mothers who usually make lamang on special days and know the meaning of lamang broadcasting. Data was obtained directly from informants by coming to Nagari Sariak Alahan Tigo, Solok Regency. Data description through data validity with a process of testing validity, reliability and objectivity. The data is analyzed using data reduction, display and verification conclusions. The results of this research are the ingredients for lamang broadcastang, broadcast rice, brown sugar, talang (bamboo), coconut, salt, vanilla and coconut water. The preparation tools used are everyday equipment, while the processing tools used are stoves and frying pans, the tools for taking gutters are saws and machetes. The processing technique used to make lamang broadcastang is grilling. Lamang broadcastang has meaning at certain events including, at a wedding event, the sumandan asks for lamang broadcastang at the house of the Daro child, this is meaningful as a ritual symbol to honor the ancestors of the ancestors in sariak alahan tigo. At the event commemorating the 100th anniversary of the death of Lamang Broadcasting, it is made to use as a stick for people who have died. And on the occasion of welcoming the holy month of Ramadan and holidays (Eid al-Fitr and Eid al-Adha), making lamang means covering insulting words from other people who cannot afford to make lamang from an economic perspective. The quality of Lamang broadcast is that it is long, round and resembles a container made of bamboo (talang), black to purple in color, has a sweet taste, with a dense and slightly hard texture and has a distinctive aroma of bamboo (talang).